IMPLEMENTASI E-GOVERNMENT DALAM PELAYANAN KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL MAL PELAYANAN PUBLIK (MPP) DI KOTA PEKANBARU - Gusvalianti, Shintia; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The implementation of e-Government in population services at the Department of Population and Civil Registration of Pekanbaru City cannot be said to be effective so that the goals that have been set and excellent population services as expected have not been achieved. In accordance with those used in the measurement of effectiveness consisting of resources, technology and information. The obstacles found in the implementation of e-government in population services are as follows: a) Constraints in the implementation of e-government due to the limited regulation as a legal umbrella. Currently, there is no regulation that really explains in detail the mechanism for implementing e-government. There needs to be an integrated e-government policy that is tailored to the needs of each institution. b) In addition, the application of e-government in government institutions is not optimal due to the limited number of competent experts in the field of information technology. This is due to the moratorium on state civil apparatus (ASN) by the PAN-RB Ministry, including for the formation of experts in the field of informatics engineering. The existence of this ASN moratorium causes a shortage of human resources for the implementation of e-government. c) In addition, the lack of accuracy from the apparatus in working has resulted in the apparatus entering incorrect data and incorrectly recording the fingerprints of the population caused by the unsanitary apparatus erasing the fingerprints of the previous population, so that the NIK data and the resident's e-KTP data do not match and There is dual ownership of fingerprints. b) External constraints, the obstacle that occurs is that sometimes the ribbon for printing the e-KTP that comes does not match the demand, so people have to be patient to wait for the ribbon to come back and population services are also hampered. Keywords: E-Government and Services Disdukcapil Pekanbaru